The factors that influence spending behaviours among workers at Mahkota Medical Center / Khairulbariyah Samsuddin and Suzanna Hasan Mydin - Samsuddin, Khairulbariyah; Hasan Mydin, Suzanna (Faculty of Business and Management, 2014)
Most of the Malaysian nowadays are been declare bankruptcy in early age. The main factors why they been declare as bankruptcy is because due to high in debt. The objective of this paper to identify factors that influence spending behavior among workers at Medical Mahkota Centre. Three factors had been selected as independent variable which are individual, economic and income. 86 of questionnaire has been distribute and the data has been analysed using Statistical Package for Social Science (SPSS). The result of this research revealed that individual (0.001), economic (0.029) and income (0.000) were significantly influence the spending behaviour of workers at Mahkota Medical Centre. This research finding will help people to plan their expenditure and avoid high debt in order to be free from been declare as bankruptcy. The findings also might help us to ensure that our economy will be in good conditions.